The Importance of Endospore-Forming Bacteria Originating from Soil for Contamination of Industrial Food Processing - Marc Heyndrickx (Applied and Environmental Soil Science)
Specific endospore formers have become important contaminants in industrial food processing. The direct or indirect soil route of contamination or dispersal is the start of events or processes in the agrofood chain that eventually leads to important problems or concerns for food safety and/or quality. Three important food sectors are discussed in this paper. In the dairy sector, Bacillus cereus, the most important pathogen or spoilage organism in this sector, and Clostridium tyrobutyricum, the most important spoiler in certain cheeses, both contaminate pasteurized milk through the faecal and/or (at least for B. cereus) the direct soil route. In the fruit juice industry, Alicyclobacillus acidoterrestris, present on raw fruits, has become a major quality-target organism. In the ready-to-eat food sector, B. cereus and other aerobic endospore formers are introduced via vegetables, fruits, or herbs and spices, while anaerobic spore formers like nonproteolytic Clostridium botulinum and Clostridium estertheticum pose safety and spoilage risks in chilled packaged foods, respectively.